Safety During Ureteroscopy: Radiation, Eyes, and Ergonomics - Miller, David T.; Semins, Michelle J. (Frontiers in Surgery, 2021)
It is known that urologic surgeons are at risk of work-place injury due to the physical requirements of operating and exposure to hazards such as body fluids, laser energy and ionizing radiation. Herein, we summarize the latest evidence regarding these risks and their effects on the urologist. We then discuss evidence-based principles to mitigate these risks including the practice of keeping radiation usage in the operating room as low as reasonably achievable, donning lead aprons, protective glasses, and practicing sound surgical ergonomics.